PENGEMBANGAN BUDI PEKERTI DAN MOTIVASI BELAJAR UNTUK MENINGKATKAN NILAI AKADEMIK SISWA SMK NURUL HUDA BAROS KOTA SERANG - Sudiharto, Sudiharto; Anwar, Rijatul; Hudri, M.; Atiah, Atiah; Febrianti, Ruli Eka (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service program aims to improve the character values and learning motivation of students at SMK Nurul Huda Baros in Serang City. The activity was conducted based on the findings that students’ academic achievement was affected by low discipline, limited learning awareness, and low motivation to study. The methods used in this program included motivational seminars, character education workshops, group discussions, and mentoring sessions on learning strategies. The results of the activity showed significant positive changes in students’ discipline, participation in learning activities, and motivation to complete academic tasks. Teachers also reported an improvement in the classroom learning atmosphere. Therefore, this program has a strong contribution in fostering positive academic behavior and is recommended to be carried out continuously in collaboration with schools.